(untitled) (American & British Studies Annual, 2022)
While the crime genre may have seemed as purely masculine for the greater part of its history, feminist critics looking for the roots of female crime writing have found a rich history of both the woman crime writer as well as the woman detective. Since the 1980s there has been not only a pronounced resurgence of interest in crime fiction, but also a boom of female detectives created by female writers. Focusing on works by Robert Galbraith, Denise Mina, Linda Barnes, Dana Stabenow and S. J. Rozan, this article explores some of the ways the traditionally masculine private eye subgenre can be appropriated to accommodate a female protagonist. Comparing a variety of protagonists and narrative strategies, it further argues that, perhaps paradoxically, the originally dominantly masculine hardboiled PI tradition seems well accommodating to female (even feminist) appropriations.